A Newly diagnosed advanced HIV infection in an older female in Poland - Wojciech Homa; Joanna Wanat; Piotr Homa; Adam Kobiernik; Jakub Rezmer; Inga Wasilewska; Justyna Stempkowska‑Rejek (Kazimierz Wielki University, 2024)
This paper presents the diagnostic and therapeutic challenges encountered in an older woman with advanced HIV infection. Upon admission, the patient exhibited severe symptoms of interstitial pneumonia and cachexia. During hospitalization, the patient was diagnosed with SARS-CoV-2 infection and a wide spectrum of opportunistic pulmonary infections, including Pneumocystis jiroveci, Candida krusei, and Staphylococcus haemolyticus. Another major diagnostic challenge posed the patient's prolonged fever, which persisted despite comprehensive treatment. This report underscores the importance of considering new HIV infections in older patients presenting complex clinical pictures, its significant mortality risk in older individuals, and the need for timely initiation and adjustment of antiretroviral therapy.